2021
DOI: 10.3390/ijerph18179031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Burnout in Primary Care Physicians in Catalonia

Abstract: Background: Recent demands to raise the clinical quality, improve the patient experience, and decrease costs have progressively increased burnout among primary care physicians. This overstretched situation has been greatly aggravated since the onset of the COVID-19 pandemic. The aim of the study is to analyse the prevalence of burnout among primary care physicians and to assess the impact of the COVID-19 pandemic on burnout. Methods: This was a multicentre longitudinal descriptive study of occupational factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
3
17
1
4
Order By: Relevance
“…When we look at the studies in other countries, in a study comparing the burnout of primary care physicians by years, it was shown that the biggest change was the decrease in PA, like in our study (Seda-Gombau et al, 2021). As a result of the analysis, before the pandemic, an upward trend for EE and DP and a downward trend for PA were observed and then aggravated by the prolongation of the pandemic (Seda-Gombau et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…When we look at the studies in other countries, in a study comparing the burnout of primary care physicians by years, it was shown that the biggest change was the decrease in PA, like in our study (Seda-Gombau et al, 2021). As a result of the analysis, before the pandemic, an upward trend for EE and DP and a downward trend for PA were observed and then aggravated by the prolongation of the pandemic (Seda-Gombau et al, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…When we look at the studies in other countries, in a study comparing the burnout of primary care physicians by years, it was shown that the biggest change was the decrease in PA, like in our study (Seda-Gombau et al, 2021). As a result of the analysis, before the pandemic, an upward trend for EE and DP and a downward trend for PA were observed and then aggravated by the prolongation of the pandemic (Seda-Gombau et al, 2021). Although we could not observe this trend with the data in our study, one year after the first case in Turkey (March 11, 2020), a decrease in PA was observed in our study, which can be explained by the prolongation of the pandemic.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A study of 40 Catalan general practitioners (GP) showed the mental health impact of the pandemic on doctors, with a significant increase in severe burnout from 10% before the pandemic in 2019 to 50% during the pandemic in October 2020 ( Seda-Gombau et al, 2021 ). In Singapore, a study of 257 GPs found anxiety (21%), depression (26.6%), and burnout (82%) ( Lum et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%